Association between serum Klotho levels and hypothyroidism in older adults: NHANES 2007–2012 - Yan Wang; Ben Hu; Suyun Yang (Scientific Reports)
Abstract Whether Klotho plays any role in hypothyroidism is unknown. This study aimed to determine the relationship between serum Klotho levels and hypothyroidism in older adults. From the 2007 to 2012 National Health and Nutrition Examination Survey (NHANES), 1444 older adults aged 65–79 were included in this cross-sectional study. Hypothyroidism was diagnosed using participants' reports of current medications and TSH tests. Klotho was measured using an enzyme-linked immunosorbent assay. The relationship between serum Klotho levels and hypothyroidism in older people was analyzed by one-way analysis of variance, multiple linear regression models, subgroup analyses, interaction tests, smoothed curve fitting, and threshold effects. A total of 209 (14.47%) participants were identified as having hypothyroidism. Serum Klotho (ln transformation) is independently and significantly negatively associated with the risk of hypothyroidism after complete adjustment for confounders (OR = 0.49, 95% CI 0.31–0.80; P = 0.0039). The results remained stable based on subgroup analyses and interaction tests. However, we observed an inverted U-shaped curve between the two using a smoothed curve fitting in the subgroups of 70 < age ≤ 75 years and females, with inflection points of 6.26 and 6.17, respectively. The results of our study indicate that serum Klotho levels negatively correlate with hypothyroidism among older adults.